Clinical effect of Astragalus membranaceus Injection on viral myocarditis in children: An overview of systematic reviews and evidence mapping - Xiaoshan Hui; Shiqi Wang; Shichao Lu; Yongmei Liu; Zhen peng Zhang; Wen jing Lian; Hui Zhang; Si yuan Zhou; Jinsheng Zhang; Jie Wang (Elsevier, 2023)
Objective: Viral myocarditis in children (VMCC) is a severe condition that requires effective treatment options. Astragalus membranaceus Injection (AMI) has been widely used for the treatment of VMCC and has shown promising results. In light of this, we conducted an overview of systematic reviews (OoSRs) and meta-analyses of randomized controlled trials (RCTs) to provide a comprehensive summary of the available evidence regarding the efficacy and safety of AMI in treating VMCC. Methods: We conducted a thorough search of 8 databases up until November 18th, 2022 to identify all systematic reviews (SRs) pertaining to the use of AMI for VMCC. We assessed the methodology quality, report quality, and evidence quality of the retrieved SRs using the AMSTAR-2, PRISMA, and GRADE frameworks. For meta-analysis, we used either a fixed-effects or a random-effects model to calculate effect sizes and 95% confidence intervals (CI) with Stata version 12.0, based on the number of original trials. We presented general results in evidence maps utilizing bubble plots. Results: A total of 4 SRs, comprising 115 RCTs and 9048 patients, were determined to be eligible for inclusion in OoSRs. Our findings revealed moderate-certainty evidence that combining AMI with western medicine (WM) improved the effective rate, cure rate and electrocardiogram results, while reducing creatine kinase, creatine kinase-MB, and lactate dehydrogenase levels for VMCC compared to the WM group. Furthermore, combination therapy did not increase adverse drug reactions[RR=0.79, 95%CI (0.44, 1.40), P>0.05] for VMCC. Evidence maps demonstrated that combining AMI with WM was more advantageous for treating VMCC. Conclusion: AMI is a valuable therapeutic option for VMCC, demonstrating remarkable efficacy and a favorable safety profile. However, to confirm these findings and determine the optimal dosing and administration regimens, further prospective studies are necessary. Our work provides a foundation for future research on this topic. While our findings support the effectiveness and safety of combining AMI with WM for treating VMCC, caution should be exercised in interpreting these results due to the quality of the current literature. Larger-scale, well-designed studies are necessary to confirm the results and provide high-quality evidence.To advance the management and outcomes of VMCC within the context of Chinese medicine, our study highlights the need for ongoing research efforts in this area. We believe that additional research will expand our understanding of the mechanisms underlying the effects of AMI and WM on VMCC, and ultimately benefit patients with this condition.